Measuring Tolerance for Ambiguity: A German-Language Adaption and Validation of the Tolerance for Ambiguity Scale (TAS) - Almuth Lietz (Measurement Instruments for the Social Sciences, 2023)
Tolerance for Ambiguity (TA)—the ability to deal with ambiguous stimuli or situations—represents a central construct for the acceptance of diversity. Although TA can be an important indicator for the functioning of a pluralistic society, it is rarely included in population surveys in Germany, and there are few validated measurement instruments for the German-language area that are suitable for general population surveys. Therefore, this paper proposes a measurement instrument in the German language to address these concerns. This development is based on the English-language Tolerance for Ambiguity Scale (TAS), which is surveyed with 12 items covering four sub-dimensions: valuing diverse others, change, challenging perspectives, and unfamiliarity. These items were translated into German using the TRAPD approach and empirically tested in a three-wave online panel study in Germany (n = 1,370 in each wave). To evaluate the psychometric quality of the translated TAS, validity (factorial and construct validity) and reliability (McDonalds’s omega coefficient and test-retest stability) are considered. This article makes at least two contributions. First, it proposes a German-language version of TAS, and second, it tests the scale using a confirmatory approach to factor analysis rather than the exploratory approaches used in previous studies. In summary, the German TAS is a valid and reliable instrument for measuring TA in population surveys in Germany.